Analisis Pengaruh Perubahan Ukuran Cam Lobe Lift terhadap Performa pada Mesin Otto Empat Langkah - Kurniawan, Nicholas; Soewono, Arka; Iskandar, Isdaryanto (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2020)
The modification of cam lobe lift value was studied to observe its effects on the volumetric efficiency and performance of a 4-stroke Otto engine with a displacement of 150 cc. The testing was done by comparing the standard cam lobe with 7,36 mm lift and two other cam lobes with a higher lift, which is 8,24 mm and 8,53 mm. ANSYS software was used as a method to acquires the volumetric efficiency value, while a dynamometer was used to measures the performance. From the calculation and testing that has been done, the usage of both modification cam lobes increase the volumetric efficiency and performance of the engine. Compared with the standard cam, the cam with 8,53 mm lift result in an increase of volumetric efficiency from 78,51% to 84,1% and performance from 15,36 WHP to 15,76 WHP at 9000 rpm.